2017
DOI: 10.1016/j.nucmedbio.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of 64Cu-DOTA-scFv-anti-PSMA lipid nanoparticles (LNPs): Enhanced tumor targeting over anti-PSMA scFv or untargeted LNPs

Abstract: Introduction Single chain (scFv) antibodies are ideal targeting ligands due to their modular structure, high antigen specificity and affinity. These monovalent ligands display rapid tumor targeting but have limitations due to their fast urinary clearance. Methods An anti-prostate membrane antigen (PSMA) scFv with a site-specific cysteine was expressed and evaluated in a prostate cancer xenograft model by Cu-64 PET imaging. To enhance tumor accumulation, the scFv-cys was conjugated to the co-polymer DSPE-PEG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…This impacts the safe dose and side effect profile of PSMA‐targeted therapy because ultimately significant radiation damage to nontarget organs needs to be avoided. Renal uptake of [ 68 Ga]Ga‐PSMA‐617 is partially due to the route of excretion of the agent and due to specific uptake from the expression of PSMA‐617 in mouse proximal renal tubules . The observation of high kidney radioactivity and uptake depicted in Figure indicated rapid renal clearance of the [ 68 Ga]Ga‐PSMA‐617‐ME from the system and shows a classic clearance curve for radiopharmaceuticals with a much faster clearance through the kidney into the bladder than reported for [ 68 Ga]Ga‐PSMA‐617 alone …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…This impacts the safe dose and side effect profile of PSMA‐targeted therapy because ultimately significant radiation damage to nontarget organs needs to be avoided. Renal uptake of [ 68 Ga]Ga‐PSMA‐617 is partially due to the route of excretion of the agent and due to specific uptake from the expression of PSMA‐617 in mouse proximal renal tubules . The observation of high kidney radioactivity and uptake depicted in Figure indicated rapid renal clearance of the [ 68 Ga]Ga‐PSMA‐617‐ME from the system and shows a classic clearance curve for radiopharmaceuticals with a much faster clearance through the kidney into the bladder than reported for [ 68 Ga]Ga‐PSMA‐617 alone …”
Section: Resultsmentioning
confidence: 81%
“…There is therefore a medical need to develop drug delivery systems that selectively transport antitumour drugs or radiopharmaceuticals into the tumour cells. Delivery systems, which have demonstrated improved therapeutic index with minimal side effects, are micelles, liposomes, lipid‐based emulsions, and polymeric nanoparticles . The use of delivery systems such as swollen micelles or microemulsions (MEs) can improve the efficacy of a drug, allowing the total dose to be reduced and therefore minimise side effects and toxicity of the formulated compound…”
Section: Introductionmentioning
confidence: 99%
“…They penetrate cancer tissue more effectively than conventional antibodies and are likely to represent a good balance between circulation time/systemic clearance, target accumulation, and tissue penetration. PSMAtargeted diabodies were developed from the huJ591 and D2B antibodies (PSMA-targeted huJ591 cysteine-modified scFv diabody labeled with 89 Zr, PSMA-targeted cysteine-modified scFv diabody labeled with 99m Tc, PSMA-targeted huJ591 DOTA (1,4,7,10-tetraazacyclodode cane-N,N,N,Ntetraacetic acid)-cysteine-modified scFv diabody labeled with 64 Cu) and so far their usefulness was evaluated for prostate cancer diagnosis by PET and SPECT [84,88,89].…”
Section: Minibodies Diabodies Single-chain Variable Region Fragmentmentioning
confidence: 99%
“…The highly promising preclinical results in vitro were reported for scFv constructs developed from the D2B antibody and radiolabeled with 131 I ( 131 I-scFvD2B), 111 In ( 111 In-scFvD2B), 123 I ( 123 I-scFvD2B) and 124 I ( 124 I-scFvD2B) [90][91][92][93]. The PSMA-targeted scFv constructs were also developed from the huJ591 antibody (DOTA-cysteine-modified scFv fragment labeled with 64 Cu and its conjugate to DSPE-PEG micelles) for PET imaging [89]. Another studies reported that the scFvhuJ549 fragments labeled with 68 Ga ( 68 Ga-THPscFv), 99m Tc ( 99m Tc-scFv) and 89 Zr ( 89 Zr-scFv) showed also selective binding to the PSMA-expressing cells in vitro [84,94,95].…”
Section: Minibodies Diabodies Single-chain Variable Region Fragmentmentioning
confidence: 99%
“…Later on, the DOTA chelator was added to offer radiolabeling with 64 Cu. Through this research, it was proved that scFv antibodies could be utilized as therapeutic tools due to their potential of conjugation with nanoparticles as they offered enhanced anti-tumor targeting [13]. Pang B. et al (2015) designed PdCu tripods with a conformal Au shell.…”
Section: Copper-64mentioning
confidence: 99%